Analisis Persediaan Suku Cadang Dengan Metode Economic Order Quantity Pada Bengkel Asia Jaya Motor Karawang - Desniyanti Manik; Rika Kartika; Salma Aulia Mulyawati; Sulistyaningsih Sulistyaningsih; Ujang Suherman (Pusat Riset dan Inovasi Nasional, 2025)
The development of hardware and software technology has developed rapidly in recent years. Currently, companies are still experiencing difficulties in processing data and information. Spare parts that are not available when needed can hinder maintenance and repair plans. For this reason, controlling spare parts inventory in the Asia Jaya Motor workshop company is very necessary to maintain the quality of goods. Asia Jaya Motor Workshop is a business operating in the automotive sector, where this place cannot be separated from an accurate information system. However, data management still uses manual methods, seeing the problems that occur at the Asia Jaya Motor Karawang Workshop, very high accuracy, convenience and speed are needed. The aim of this research is to obtain an effective and efficient spare parts inventory analysis so that spare parts procurement and control plans can be accurate in supporting maintenance and repair programs. The data collection techniques for this research are library research and field research. So, the total cost of spare parts inventory in the 2011-2014 period according to the Economic Order Quantity method for each spare part has increased. The total cost (total cost) of spare parts inventory according to the Economic Order Quantity method is lowest in the 2021 period and the total cost (total cost) of spare parts inventory is the highest in the 2023 period.